Front propagation and quasi-stationary distributions: two faces of the same coin? - Groisman, Pablo Jose (2019)
We analyze the connection between front propagation and quasi-stationary distributions in translation invariant one-dimensional Markov processes. We describe the link between them through the microscopic models known as Branching Brownian Motion with selection and Fleming–Viot.